Perspectives on genetic resources at the Fungal Genetics Stock Center. - Kevin McCluskey; Michael Plamann (Fungal Genetics Reports, 2008)
The Fungal Genetics Stock Center has been banking and distributing resources for work with genetically characterized fungi since 1960. While most of the collection consists of strains of Neurospora, an NIH model filamentous fungus, the past fifteen years has seen the collection expand to include plant and human pathogenic fungi. The use of the resources in the collection has grown over the last 10 years as well, reflecting both a growth in research using standardized materials as well as the development of new materials through molecular genetic technology. This growth is not limited to newly deposited materials, however, and includes renewed interest in particular classes of strains with characteristics that were not recognized when they were originally deposited. One significant example is the use of strains carrying the osmotic-2 lesion in Neurospora crassa. This, and other utilization trends, underscores the need to provide strong support to the continued and expanded biobanking effort in the US.